Notary Liability on Contract Renegotiation in Business Contracts - Ni Nengah Dwi Dharmayanthi; Benny Djaja; Maman Sudirman (Publikasi Indonesia, 2024)
A notary is a public official who is given the mandate to make authentic deeds, one of which is through business contracts. In practice, business contracts often experience various updates for one reason or another. As part of a notary's duties to make business contract deeds, the notary also has the responsibility to ensure that all procedures and contract clauses do not conflict with the law. This research will discuss considerations about the role of notaries in preparing business contract documents, potential sources of disputes related to the implementation of business contracts and provisions for resolving disputes related to business contract deeds. To discuss this problem, an empirical juridical approach will be used through analytical descriptive research. The research concludes that the presence of a notary takes into account the interests of the parties when drafting business contract deeds so that they can anticipate possible conflicts that may arise. The authenticity of a notarial deed becomes absolute with the commitment of the parties concerned to continue to rely on consultation and agreement in resolving disputes that may arise.